2020
DOI: 10.1016/j.biochi.2020.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RNA binding properties of human Ku protein reveals its interactions with 7SK snRNA and protein components of 7SK snRNP complex

Abstract: Analysis of RNA binding properties of human Ku protein reveals its interactions with 7SK snRNA and protein components of 7SK snRNP complex, Biochimie,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 90 publications
(118 reference statements)
4
7
0
Order By: Relevance
“…Additionally, we observed BCL11b is associated with proteins involved in DNA repair and cellular response to stimuli (such as BRCA2, MCMs, PARP1, and SMCs proteins). In agreement to our results, BCL11b was previously shown to interact with Ku70 and Ku80 proteins, which have an important role in the non-homologous end-joining DNA repair pathway (Shadrina et al, 2020).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, we observed BCL11b is associated with proteins involved in DNA repair and cellular response to stimuli (such as BRCA2, MCMs, PARP1, and SMCs proteins). In agreement to our results, BCL11b was previously shown to interact with Ku70 and Ku80 proteins, which have an important role in the non-homologous end-joining DNA repair pathway (Shadrina et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…In agreement to our results, BCL11b was previously shown to interact with Ku70 and Ku80 proteins, which have an important role in the non-homologous end-joining DNA repair pathway (Shadrina et al, 2020).…”
Section: Bcl11b Interacts With Proteins Dedicated To Genetic and Epigsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies focusing on autophosphorylation of DNA-PKcs have indicated that while DNA-PKcs PQR/PQR mice were healthy, DNA-PKcs 5A/5A and DNA-PKcs 3A/3A mice showed bone marrow failure [ 34 , 53 ]. The fact that Ku binds to both DNA and RNA [ 65 , 66 ], and that the Ku complex and DNA-PKcs localize in the nucleolus in the absence of DNA damage [ 67 ], suggests that DNA-PK may act in an RNA-dependent manner in the nucleolus. Indeed, an analysis using v-ABL kinase-transformed pro-B cell lines from DNA-PKcs kd/kd and DNA-PKcs 3A/3A mice revealed that translation is reduced in these cells [ 34 ].…”
Section: Effects Of Dna-pkcs On Development and Differentiation Determined By Comparing Knockout And Mutant Micementioning
confidence: 99%
“…In particular, it is known that DNA-PK may phosphorylate the C-terminal domain of RNAP II [ 74 ], and, along with the Ku70/Ku80 heterodimer, DNA-PKcs may be precipitated from human cells together with the RNAP II holoenzyme [ 160 ]. It has also been shown that the Ku70/Ku80 heterodimer may interact with hairpin RNA involved in transcription performed by RNAP II, HIV-1 TAR PHK and 7SK PHK [ 159 , 161 , 162 ], whereas the catalytic subunit of DNA-PKcs forms a complex with HIV-1 Tat [ 163 ] and may phosphorylate it [ 164 ]. These various data indicate the possible involvement of the DNA-PK DNA repair complex in the regulation of transcription from the HIV-1 promoter.…”
Section: Dna-pk Targets In Hiv Replicationmentioning
confidence: 99%